AN EOQ MODEL FOR ITEMS THAT ARE BOTH AMELIORATING AND DETERIORATING WITH LINEAR INVENTORY LEVEL DEPENDENT DEMAND (FUDMA JOURNAL OF SCIENCES, 2023)
It is normally observed in real life that the volume of stocked items have motivational effect on customers. Stores with large amount of displayed items attract buyers more than stores with scanty items. In this study therefore, we develop an EOQ model for linear inventory level dependent demand for items that undergo both deterioration and amelioration at the same time while at inventory level with no shortage of items. The poultry, fishery, piggery, and so on where the stock increase in weight and/or value within a short time and decrease in volume due to diseases or other factors provide good example. The model determines the best cycle length so as to minimize the overall cost. Numerical examples are given to illustrate the model and a sensitivity analysis carried out to see the effect of changes to some model parameters on the decision variables.
Keywords: EOQ; Amelioration; Deterioration; Partial backlogging; Linear level inventory demand